Design and Simulation of the Control System for Inverter-fed Permanent Magnet Synchronous Motor Drive - Ramana Pilla; Santukumari Killari; K.B.Madhu Sahu (Institute of Advanced Engineering and Science, 2018)
Development in the field of power electronics, cost effective DSP’s and microprocessors have opened a new era in the design and implement modern control strategies for variable speed drives. This paper presents the design of a control system which includes a non-linear controller and observer for inverter fed Permanent Magnet Synchronous Motor (PMSM) Drive. The entire design is carried out by designing of Speed Controller, Non-linear controller (NLC), State feedback controller (SFC), H∞ controller as well as Non-linear full order observer (NFO). The proposed control scheme is extensively simulated under various conditions using MATLAB/Simulink, which shows better performance under all operating conditions for variable speed PMSM drive.